Cluster Randomized Controlled Trial: Clinical and Cost-Effectiveness of a System of Longer-Term Stroke Care - Forster, Anne (Stroke, 2015)
BACKGROUND AND PURPOSE—: We developed a new postdischarge system of care comprising a structured assessment covering longer-term problems experienced by patients with stroke and their carers, linked to evidence-based treatment algorithms and reference guides (the longer-term stroke care system of care) to address the poor longer-term recovery experienced by many patients with stroke. METHODS—: A pragmatic, multicentre, cluster randomized controlled trial of this system of care. Eligible patients referred to community-based Stroke Care Coordinators were randomized to receive the new system of care or usual practice. The primary outcome was improved patient psychological well-being (General Health Questionnaire-12) at 6 months; secondary outcomes included functional outcomes for patients, carer outcomes, and cost-effectiveness. Follow-up was through self-completed postal questionnaires at 6 and 12 months. RESULTS—: Thirty-two stroke services were randomized (29 participated); 800 patients (399 control; 401 intervention) and 208 carers (100 control; 108 intervention) were recruited. In intention to treat analysis, the adjusted difference in patient General Health Questionnaire-12 mean scores at 6 months was −0.6 points (95% confidence interval, −1.8 to 0.7; P=0.394) indicating no evidence of statistically significant difference between the groups. Costs of Stroke Care Coordinator inputs, total health and social care costs, and quality-adjusted life year gains at 6 months, 12 months, and over the year were similar between the groups. CONCLUSIONS—: This robust trial demonstrated no benefit in clinical or cost-effectiveness outcomes associated with the new system of care compared with usual Stroke Care Coordinator practice. CLINICAL TRIAL REGISTRATION—: URL: http://www.controlled-trials.com. Unique identifier: ISRCTN 67932305.